SISTEM INFORMASI MANAJEMEN PERSEDIAAN DENGAN FUNGSI GRAFIK STATISTIK PERUSAHAAN PENJUALAN MOTOR BERBASIS CLIENT-SERVER - Arsito Ari Kuncoro; Febryantahanuji Febryantahanuji; Zaenal Mustofa (Jurnal Publikasi Ilmu Komputer dan Multimedia, 2023)
Utilization of client server technology in inventory information systems is very effective and efficient, because client server is a form of architecture, where the client is a receiving device that will display and run applications (computer software) and a server is a device that provides and acts as an application manager, data , and security. Companies engaged in the field of motorcycle units of any brand which usually also sells motorcycle spare parts, and motorcycle service services. The process of collecting data on motorbikes for companies engaged in the sale of motorbikes is still carried out with simple records. Data entry and exit of motorbikes is recorded in a book and then inputted manually so it is less efficient because it takes a long time for the data entry process. Motor data storage is still in the form of a separate file so that data can be lost and easily damaged. Searching for data takes a long time because it has not been stored on a special server and the lack of security from irresponsible parties has resulted in the process of making sales/expense reports and requesting reports for motorcycle sales companies to be ineffective and inefficient.